Pengaruh Gaya Hidup dan Penerimaan Teknologi Informasi Terhadap Kepuasan Nasabah dalam Bertransaksi Non Tunai Melalui Mobile Banking Bank Kalsel - Akhlakulkarimah, Artesya Nanda; Ghalib, Saladin (Universitas Lambung Mangkurat, 2023)
Banking companies, as a financial services industry, are always improving in order to keep up with the trends and assist the National Non-Cash Movement. As one of the financial services sectors in South Kalimantan Province, PT. Bank Pembangunan Daerah Kalimantan Selatan continues making actions to contribute to the provision of beneficial products for consumers, one of which is mobile banking. Because of client requirements and bank technology assistance, mobile banking has become the preferred method of non-cash transactions for most people. The goal of this study is to investigate and analyze the relationship between lifestyle and the acceptance of information technology on consumer satisfaction. Bank Kalsel Banjarmasin Main Branch was chosen as the research location. Non-probability sampling was employed to pick 341 respondents. A questionnaire was utilized to collect data, and multiple linear regression was applied to test the hypothesis. The findings revealed that lifestyle had no influence on customer satisfaction. Customer satisfaction was significantly affected by acceptance of information technology. Customer satisfaction was greatly affected by lifestyle and acceptance of information technology. Keywords: lifestyle, acceptance of information technology, customer satisfaction